Watch and learn: imagery design process for weaving crafts / Zainab Anuar … [et al.] - Anuar, Zainab; Ahmad, Nani Hartina; Wan Sulaiman, Wan Salwana; Mohd Hasan, Adib; Daud @ Ismail, Yusof (Faculty of Art and Design, 2024)
Weaving craft is one process that produces woven textile products that can be constructed by hand or machine. Different theories and techniques for putting forth ideas lead to distinctive products among textile designers. New designers or weavers were unable to deduct the design process, particularly in woven textiles, from the existence of a textile designer due to a lack of references. This paper shows the weaving design process of woven textile art making to form the imagery weaving as its surface design. The primary objective of the warp-paint procedure is to emphasise the design image on the woven surface. The design process can be done manually by integrating the research into the subject matters, motif development, and the weaving process. The most detailed part of this research will be on the weaving process which shows the warp-paint colouring technique as the main approach to form the imagery weaving. The methodology would be carried out by incorporating a qualitative approach, which would involve literature reviews, interviews, observations, and fieldwork. The output of this article will serve as a resource for aspiring new weavers or textile designers who want to use the suggested idea to produce woven products with imagery design patterns. According to the study's findings, this approach calls for knowledge of weaving procedures and weaving handling expertise to make the intended image more clearly visible on the weave's surface.